2002
DOI: 10.1002/hec.759
|View full text |Cite
|
Sign up to set email alerts
|

Public spending on health care and the poor

Abstract: This paper uses new cross-country data to assess the relationship between public spending on health care and the health status of the poor. Data are drawn from two sources: (i) existing data on health status by income quintile tabulated from demographic health surveys in 44 countries; and (ii) our estimates of the health status of the poor in over 70 countries drawn from a new technique in decomposing social indicators. Our estimates confirm that the poor have significantly worse health status than the nonpoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
4
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 16 publications
11
100
4
10
Order By: Relevance
“…While the distribution of the subsidy is not pro-poor, the subsidy can still shift the distribution of health care in a pro-poor direction. These hypotheses are consistent with evidence showing that public spending has no significant effect on health of the non-poor but a positive marginal impact on the health of the poor (Bidani and Ravallion 1997;Gupta et al 2003;Wagstaff 2003). The evidence shows that, on average, the better-off typically receive most of the subsidy.…”
Section: Inequalityincreasingsupporting
confidence: 86%
“…While the distribution of the subsidy is not pro-poor, the subsidy can still shift the distribution of health care in a pro-poor direction. These hypotheses are consistent with evidence showing that public spending has no significant effect on health of the non-poor but a positive marginal impact on the health of the poor (Bidani and Ravallion 1997;Gupta et al 2003;Wagstaff 2003). The evidence shows that, on average, the better-off typically receive most of the subsidy.…”
Section: Inequalityincreasingsupporting
confidence: 86%
“…This is especially important for developing countries as improving the health status of their citizens could substantially ameliorate their economic performance. Moreover, it has been shown that public spending on health care matters more for the poor in general (Gupta et al, 2003). Finally, this paper is innovative as it examines the effects of natural resources on inputs rather than human development outcomes as the latter might reflect factors beyond policymakers' control.…”
Section: Discussionmentioning
confidence: 99%
“…The lower health expenditures in resource-rich countries therefore represent an important missed opportunity to use natural resource wealth to secure long term economic prosperity. Moreover, the importance of public health expenditures goes beyond the mere economic consequences, as it entails wide-ranging social implications and can be crucial in alleviating poverty (Gupta et al, 2003). This paper focuses on inputs rather than health outcomes, as to grasp to what extent governments in resource-rich countries fail to prioritize policies geared towards the poor and human development.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nor do the two studies cited here. They estimate the distribution of effects under sometimes strong assumptions -discussed in Gupta et al 2003. 19 under-estimation of the beneficial effects of health expenditure , and I have argued that this might explain some of the negative findings in the literature. The identified effect is robust to controls for state-specific rainfall shocks and other state-level variables including education, inequality and media prevalence.…”
Section: Discussionmentioning
confidence: 99%